Screening Criteria for the Indonesian Sharia Stock Index: An Analysis Based on Monzer Kahf’s Paradigm - Alwa, Moh. Abdul Aziz; Amin Wahyudi (Journal of Islamic Economics (JoIE), 2024)
Introduction: The topic in this journal is related to the Indonesian government's policy in providing categorization of Sharia stock indices which have criteria for debt levels below 45% compared to total assets. It has a big difference compared to the major stock exchanges in the UK, USA, Malaysia, Qatar and Pakistan which have a debt ownership limit of 30%-33%. Research Methods: This study uses a qualitative approach method, this study focuses on hypothesis testing. Experimental research is used in a quantitative method because the financial ratio data obtained from IDX will be controlled and manipulated by the author so as to obtain the effectiveness of one of the variables. Results: There is a difference of 21% of the number of Sharia shares in Indonesia when using the rule of debt ownership of a maximum of 30% of assets. Conclusion: Hopefully, this research can give an overview of the IDX that Indonesia is still permissive so that if it is enforced, it can provide peace of mind for Muslim investors in Indonesia.